2019
DOI: 10.1002/chem.201904479
|View full text |Cite
|
Sign up to set email alerts
|

Cubane Electrochemistry: Direct Conversion of Cubane Carboxylic Acids to Alkoxy Cubanes Using the Hofer–Moest Reaction under Flow Conditions

Abstract: The highly strained cubane system is of great interest as a scaffold and rigid linker in both pharmaceutical and materials chemistry. The first electrochemical functionalisation of cubane by oxidative decarboxylative ether formation (Hofer–Moest reaction) was demonstrated. The mild conditions are compatible with the presence of other oxidisable functional groups, and the use of flow electrochemical conditions allows straightforward upscaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…[7] This mode of operation significantly simplifies the technical requirements of the setup, as a three-electrode electrochemical cell or a potentiostat are not required (an inexpensive adjustable power supply can be employed instead). [17] Moreover, the reaction selectivity can still be optimized by tuning the current density at the electrodes.…”
Section: Flow Electrolysis Cell Performance Decarboxylative Methoxylmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] This mode of operation significantly simplifies the technical requirements of the setup, as a three-electrode electrochemical cell or a potentiostat are not required (an inexpensive adjustable power supply can be employed instead). [17] Moreover, the reaction selectivity can still be optimized by tuning the current density at the electrodes.…”
Section: Flow Electrolysis Cell Performance Decarboxylative Methoxylmentioning
confidence: 99%
“…[16] These types of electrode materials (Pt and C) have also been previously utilized for Hofer-Moest reactions in continuous flow mode. [17] In our investigation, graphite was selected as the anode material and stainless steel as the cathode. Preliminary batch experiments showed that these materials perform well in the presence of a catalytic amount of NaOMe as the base for the electrolysis of 1.…”
Section: Flow Electrolysis Cell Performance Decarboxylative Methoxylmentioning
confidence: 99%
“…Along the same line, the electrochemical functionalization of 4-substituted cubane-1-carboxylic acids 33, 34, and 67 was reported. 62 The electrolysis of 4-substituted cubane-1-carboxylic acids 33, 34, and 67 initially formed the radical, which was oxidized further to yield the carbocation. The resultant carbocation reacted with nucleophiles (alcohols) to afford cubane derivatives.…”
Section: Scheme 6 Synthesis Of Cubane Redox-active Esters and Subsequmentioning
confidence: 99%
“…The anodic oxidation of 4-(methoxycarbonyl)cubane-1-carboxylic acid (67) using a C/PVDF anode (200 mA, 0.5 mL/min) in the presence of methanol and Et 3 N yielded methyl 4-methoxycubane-1-carboxylate. 62 N. Grover, M. O. Senge…”
Section: Scheme 6 Synthesis Of Cubane Redox-active Esters and Subsequmentioning
confidence: 99%
“…Further anodic oxidation of these intermediates results in highly reactive carbocations, which are prone to rearrangement, elimination or coupling with any nucleophile in their proximity 47,48 . High selectivity can only be achieved if the radical and the positive charge are stabilised by electron-donating substituents 49,50 , resonance 51,52 or conjugation with α-O 53,54 , α-N 55,56 or α-S substituents 57 . Still, the O-nucleophile is often added in large excess.…”
mentioning
confidence: 99%